Enhancing metacognitive skills in the classroom: The effect of number head together cooperative learning model - Adilah Mahmudah Eka Pratiwi; Utiya Azizah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to study the effect of the number head together NHT type cooperative learning model on the activities of students and metacognitive skills. The research subjects came from students of class eleventh Science Senior High School of 19 Surabaya, 35 students using a one pretest-posttest control group design. The results obtained were 1) the percentage of implementation of the NHT cooperative learning model at meetings 1 and 2 was 94.4% and 95.8%, which were categorized as very good. 2) The percentage of student activity at the relevant 1 and 2 meetings is 95.97% and 97.20%, respectively. 3) Increased N-gain on students' metacognitive skills through post-test, including planning skills of 0.6; monitoring skills of 0.5; and evaluating skills of 0.5.